Penggunaan Fitur Close Friends Pada Second Account Instagram Sebagai Self Disclosure (Studi Dramaturgi Di Kalangan Mahasiswa Ilmu Komunikasi Universitas Nusa Cendana) - falukas, stevy shania (Widya Komunika, 2025)
This research aims to find out the meaning and use of the use of the close friends feature on the second Instagram account of Nusa Cendana University Communication Science students and to see the display of self-disclosure carried out through the close friends second account feature and also to describe how messages are managed on the front stage and back stage in the close friends second account Instagram feature of Nusa Cendana University Communication Science students on the first and second Instagram accounts. This type of research is a type of qualitative descriptive research where the researcher carries out observations, interviews and documentation with several informants. The theory used is Erving Goffman's Dramaturgical Theory. The results of this research show that Nusa Cendana University Communication Science students interpret and utilize, display self-disclosure and manage messages using the close friends second account feature on Instagram because they want to separate their formal personal life from their daily activities which are more flexible, they want to brand themselves well on their first account while being more self-disclosure or open self-disclosure on the close friends second account feature on Instagram by separating only trusted people who can see their Instagram stories. With that, posting random things, private things, togetherness with family and friends, romantic relationships and their work is included in the back stage of Dramaturgical theory, while posting formal things such as birthday greetings, aesthetic photos of oneself is included in the front stage of Dramaturgical theory.